2021
DOI: 10.3390/toxins13090606
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxins Secretion and Voltage-Gated Sodium Channel Adaptation in the Ribbon Worm Kulikovia alborostrata (Takakura, 1898) (Nemertea)

Abstract: Nemertea is a phylum of marine worms whose members bear various toxins, including tetrodotoxin (TTX) and its analogues. Despite the more than 30 years of studying TTXs in nemerteans, many questions regarding their functions and the mechanisms ensuring their accumulation and usage remain unclear. In the nemertean Kulikovia alborostrata, we studied TTX and 5,6,11-trideoxyTTX concentrations in body extracts and in released mucus, as well as various aspects of the TTX-positive-cell excretion system and voltage-gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The transferring of TTX from prey organisms has been reported in the pufferfish genus Takifugu, such as T. rubripes and T. alboplumbeus [13,14,19,40]. Alternatively, although the proposed composition of TTX and biosynthetic intermediates has been investigated in various species [41][42][43][44][45], there have been no studies on how these substances in the prey are ingested and transferred to predators. Therefore, it was speculated that various TTX-related compounds in the prey would be directly ingested and accumulated in the body of predators, such as ribbon worms and newts [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The transferring of TTX from prey organisms has been reported in the pufferfish genus Takifugu, such as T. rubripes and T. alboplumbeus [13,14,19,40]. Alternatively, although the proposed composition of TTX and biosynthetic intermediates has been investigated in various species [41][42][43][44][45], there have been no studies on how these substances in the prey are ingested and transferred to predators. Therefore, it was speculated that various TTX-related compounds in the prey would be directly ingested and accumulated in the body of predators, such as ribbon worms and newts [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1). This mutation appears to be unique among snakes (Feldman et al, 2012;McGlothlin et al, 2016), but is seen in several other TTX-resistant taxa (Geffeney et al, 2019;Gendreau et al, 2021;Jost et al, 2008;Vaelli et al, 2020;Vlasenko et al, 2021) and confers a roughly 15-fold reduction in TTX ligation to the pore (Jost et al, 2008). Additionally, we found that all Th.…”
Section: Sodium Channel Sequencesmentioning
confidence: 67%
“…couchii contain the same mutation in the skeletal muscle channel gene, SCN4A (encoding Na v 1.4): a single amino acid substitution (M1267T) in the DIII P‐loop of Na v 1.4 at a critical TTX binding site (detailed in Feldman et al, 2009) (Figure 3; Table 1). This mutation appears to be unique among snakes (Feldman et al, 2012; McGlothlin et al, 2016), but is seen in several other TTX‐resistant taxa (Geffeney et al, 2019; Gendreau et al, 2021; Jost et al, 2008; Vaelli et al, 2020; Vlasenko et al, 2021) and confers a roughly 15‐fold reduction in TTX ligation to the pore (Jost et al, 2008). Additionally, we found that all Th.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations